Exploring Experiences: University Students' and Lecturers' Engagement with Schoology for Online Assessment - Lilis Patimah; Muhammad Fauzan Aminudin; Ida Megawati; Mehvish Riaz; Anisa Putri Cahyani; Albertus Erico Jerry Krisna Nugroho; Khoirul Bariyyah (Journal of Education and Teaching (JET), 2026)
This mixed-methods research investigated how Indonesian learners and lecturers perceive Schoology, an interactive learning management system, in blended learning contexts. Through structured questionnaires and interviews involving 25 lecturers and 220 students, data were analysed using SPSS and triangulated for validity. The findings provide insights that although Schoology has strengths in its feasibility and user-friendliness for teaching and assessment, participants also reported concerns about internet reliability, trust, plagiarism, and the risk of cheating.